Clostridium botulinum Group II Isolate Phylogenomic Profiling Using Whole-Genome Sequence Data - Weedmark, K. A. (Appl Environ Microbiol, 2015)
Clostridium botulinum group II isolates (n = 163) from different geographic regions, outbreaks, and neurotoxin types and subtypes were characterized in silico using whole-genome sequence data. Two clusters representing a variety of botulinum neurotoxin (BoNT) types and subtypes were identified by multilocus sequence typing (MLST) and core single nucleotide polymorphism (SNP) analysis. While one cluster included BoNT/B4/F6/E9 and nontoxigenic members, the other comprised a wide variety of different BoNT/E subtype isolates and a nontoxigenic strain. In silico MLST and core SNP methods were consistent in terms of clade-level isolate classification; however, core SNP analysis showed higher resolution capability. Furthermore, core SNP analysis correctly distinguished isolates by outbreak and location. This study illustrated the utility of next-generation sequence-based typing approaches for isolate characterization and source attribution and identified discrete SNP loci and MLST alleles for isolate comparison.